‘Vet du ka som er en kombinasjon?’: The early linguistic choices of three children in multidialectal environments - Briksdal, Anette (Målbryting, 2025)
The research question addressed in this article is how the mothers’ dialect, the dialects of the rest of the family and in the local area, and perceptions of standard dialect influence children’s early linguistic choices. The article explores the speech patterns of three children over time and discusses the reasons behind the linguistic choices they make. Additionally, it investigates the prosodic dialect features in the children’s speech and the development of these patterns. The first participants in this project are the two girls named Sol and Snø, whose everyday interactions were recorded from ages 2;2 to 4;6. The third participant is Måne, Sol’s younger brother, whose speech was recorded from ages 1;9 to 2;9. Furthermore, the mothers of these children have contributed with observational data. As the mother of Sol and Måne, I had the opportunity to continuously collect data, while Snø’s data was gathered at three separate points with approximately a year between them. Based on this dataset, we can observe that all the children have features from their mothers’ dialect, but it varies to what degree and for how long the features are maintained. Factors as input from grandparents and older siblings, and periods of absence from kindergarten seem to influence the children’s speech. Additionally, moving to the father’s local area plays a crucial role in Snø’s language development. It is also evident that all three informants, regardless of the dialects by which they are surrounded, at different points in time orient themselves toward a form of standard dialect, perhaps experienced though roleplay and from reading aloud. In conclusion, this article explores the linguistic choices made by these children and discusses how the choices might reflect the status of the different agents of language socialization.